2003
DOI: 10.1021/jf021146f
|View full text |Cite
|
Sign up to set email alerts
|

Glycoalkaloid and Calystegine Contents of Eight Potato Cultivars

Abstract: Diverse procedures have been reported for the separation and analysis by HPLC of the two major glycoalkaloids present in potatoes, alpha-chaconine and alpha-solanine. To further improve the usefulness of the HPLC method, studies were carried out on the influence of several salient parameters on the analysis of the two potato glycoalkaloids. Effects on retention (elution, separation) times of the (a) composition and pH of the mobile phase (acetonitrile and phosphate buffer), (b) concentration of the phosphate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
115
2
9

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(137 citation statements)
references
References 54 publications
11
115
2
9
Order By: Relevance
“…The TGA contents found by us are in line with other literature data, which also indicates a significant variability in TGA ranges among cultivars. Valcarcel et al (2014) indicated a range from 4 to 957 mg/kg dry matter (DM), Friedman et al (2003) from 5 to 592 mg/kg DM, Deusser et al (2012) from 7 to 466 mg/kg DM and Petersson et al (2013) indicated normal ranges between 5 and 100 mg/kg FM.…”
Section: Glycoalkaloids Contentmentioning
confidence: 99%
“…The TGA contents found by us are in line with other literature data, which also indicates a significant variability in TGA ranges among cultivars. Valcarcel et al (2014) indicated a range from 4 to 957 mg/kg dry matter (DM), Friedman et al (2003) from 5 to 592 mg/kg DM, Deusser et al (2012) from 7 to 466 mg/kg DM and Petersson et al (2013) indicated normal ranges between 5 and 100 mg/kg FM.…”
Section: Glycoalkaloids Contentmentioning
confidence: 99%
“…In most cultivated potato species, derivatives of 3-O-glucosylsolanidine are more abundant than those of 3-O-galactosylsolanidine (Friedman et al, 2003). Interestingly, several genotypes of Solanum chacoense exhibit higher relative levels of SGT1 (galactosyltransferase) than of SGT2 (glucosyltransferase), suggesting an opposite SA 3-O-glycosylation ratio (galactosylation/glucosylation) (Krits et al, 2007).…”
Section: Game1 Acts Predominantly As a Udp-gal: Tomatidine Galactosylmentioning
confidence: 99%
“…The final method developed for extraction of glycoalkaloids from eggplant material was based on modification and consideration of the varied procedures as applied to the potato by Kuronen et al [27] Saito, [29] Friedman and Levin, [30] Dao and Friedman, [33] Sotelo and Serrano, [36] Friedman et al, [39] and as applied to Solanum sycophanta by Usubillaga et al [55] Analogous to classical precipitation/crystallization procedures for the extraction of solanine from potato, [56] initial attempts were made to extract the glycoalkaloids from eggplant by prescribed methods that involved collection of either a residue [36] or a precipitate. [39] However, such routes were abandoned because acceptable collection of a precipitate/residue of suitable purity and accurately measured mass was either not possible or not feasible, especially when considering that the final method would eventually be applied to a large set of samples.…”
Section: Extractionmentioning
confidence: 99%
“…[39] However, such routes were abandoned because acceptable collection of a precipitate/residue of suitable purity and accurately measured mass was either not possible or not feasible, especially when considering that the final method would eventually be applied to a large set of samples. Instead, it was deemed preferable to keep the extracts in solution throughout the entire analysis.…”
Section: Extractionmentioning
confidence: 99%